Patients present earlier and survival has improved, but pre-ART attrition is high in a six-year HIV cohort data from Ethiopia. - Zewdie Mulissa (Public Library of Science (PLoS), 2010)
Background Previous studies showed higher early mortality rates among patients treated with antiretroviral drugs in settings with limited resources. One of the reasons was late presentation of patients to care. With improved access to HIV services, we expect improvements in disease stage at presentation. Our objective was to assess the effect of improved availability of HIV services on patient presentation to care and subsequent pre-ART and on-ART outcomes. Methodology and principal findings At Arba Minch Hospital in Ethiopia, we reviewed baseline characteristics and outcomes of 2191 adult HIV patients. Nearly a half were in WHO stage III at presentation. About two-thirds of the patients (1428) started ART. Patients enrolled in the early phase (OR = 4.03, 95% CI 3.07-5.27), men (OR = 1.78, 95%CI 1.47-2.16), and those aged 45 years and above (OR = 2.04, 95%CI 1.48-2.82) were at higher risk of being in advanced clinical stage at presentation. The pre-treatment mortality rate was 13.1 per 100 PYO, ranging from 1.4 in the rapid scale-up phase to 25.9 per 100 PYO in the early phase. A quarter of the patients were lost to follow-up before starting treatment. Being in less advanced stage (HR = 1.9, 95% CI = 1.6, 2.2), being in the recent cohort (HR = 2.0, 95% CI = 1.6, 2.6), and rural residence (HR = 1.8, 95% CI = 1.5, 2.2) were independent predictors of pre-ART loss to follow-up. Of those who started ART, 13.4% were lost to follow-up and 15.4% died. The survival improved during the study. Patients with advanced disease, men and older people had higher death rates. Conclusions and significance Patients started to present at earlier stages of their illness and death has decreased among adult HIV patients visiting Arba Minch Hospital. However, many patients were lost from pre-treatment follow-up. Early treatment start contributed to improved survival. Both pre-ART and on-ART patient retention mechanisms should be strengthened.